Proceedings of the 2018 ACM Symposium on Eye Tracking Research &Amp; Applications 2018
DOI: 10.1145/3204493.3204579
|View full text |Cite
|
Sign up to set email alerts
|

Relating eye-tracking measures with changes in knowledge on search tasks

Abstract: We conducted an eye-tracking study where 30 participants performed searches on the web. We measured their topical knowledge before and after each task. Their eye-fixations were labelled as "reading" or "scanning". The series of reading fixations in a line, called "reading-sequences" were characterized by their length in pixels, fixation duration, and the number of fixations making up the sequence. We hypothesize that differences in knowledge-change of participants are reflected in their eye-tracking measures r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In contrast to the aforementioned studies that considered just a handful of predictors, Yu et al [51] evaluated approximately 70 search-based features as predictors of learning; individually they were found to be only weakly correlated with knowledge gain, though some (document dwell time, query complexity) were more predictive than others. Although unarguably less scalable, a number of eye-tracking measures (such as the duration or reading fixations within documents) have also shown to be predictive of learning outcomes [3,4]. Finally, we note that von Hoyer et al [46] also found learners to be able to estimate their learning performance with increasing accuracy as the search session progresses.…”
Section: Related Workmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast to the aforementioned studies that considered just a handful of predictors, Yu et al [51] evaluated approximately 70 search-based features as predictors of learning; individually they were found to be only weakly correlated with knowledge gain, though some (document dwell time, query complexity) were more predictive than others. Although unarguably less scalable, a number of eye-tracking measures (such as the duration or reading fixations within documents) have also shown to be predictive of learning outcomes [3,4]. Finally, we note that von Hoyer et al [46] also found learners to be able to estimate their learning performance with increasing accuracy as the search session progresses.…”
Section: Related Workmentioning
confidence: 75%
“…Recently, a number of different research efforts have been devoted to the area of SAL, such as: (i) the influence of user characteristics and user strategies on learning while searching [13,20,22,29,30,34]; (ii) the exploration of user behavior during learning-oriented search sessions [12,13,27,34]; (iii) the prediction/observation of how knowledge changes over time and across different cognitive levels of learning [18,21,34,49,51]; (iv) the measuring of learning during searches [3,4,12,46,50]; and (v) the design of retrieval algorithms for learning-oriented search tasks and user interface components [40,42,43]. Despite the large number of prior works in the SAL field, only a small number have so far explored the adaptation of the search system itself to improve learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya and Gwizdka (2018) [79] Users with higher change in knowledge differed significantly in terms of their total reading-sequence length, reading-sequence duration, and number of reading fixations, when compared to participants with lower knowledge change.…”
Section: Papoutsaki Et Al (2017) [8]mentioning
confidence: 98%
“…Search as Learning. Previous research within the SAL domain has focused on: (i) understanding user behaviours when undertaking a learning-oriented search task [9,17,24,29,32,36]; (ii) exploring different types of users and their behaviours (e.g., novices vs. experts) [6,17,39,44]; and (iii) the optimisation of retrieval functions for learning [47][48][49].…”
Section: Related Workmentioning
confidence: 99%